Factors Associated with Food-borne Diseases: Case in Fast Food Restaurant - Rahmayani, Sri Tanti (Kos Globalindo Group, 2019)
The purpose of this study is to investigate the factors associated with foodborne diseases in fast food restaurant food processors Garut also know as Switzerland of Java credited by Sir Charles Spenser Chaplin in 1920s. By knowing these factors, policy development can be reformulated to carry out food sanitation program in an optimal way. For this purpose, a data analytics approach is employed on the data collected based on survey on official documents and interview to three restaurantsâ€™ cooks and managers to classify their behavior during food processing. The classification consists of two levels, namely positive and negative behavior. As a result, we found that (1) the cooks in fast food restaurants have good knowledge about preventing food-borne diseases but they have a negative attitude vis-Ã -vis food-borne diseases, (2) they have no experience in preparing fast food, and (3) their educational background is at most high school or vocational high school level. The method used in this research is limited on information and cross-sectional techniques to understand the relationship between food-borne diseases and factors under study. If the previous researches focus on self-protection equipment (SPE) and cleanliness of food processing facilities, here we consider these factors; knowledge on food-borne disease prevention and attitude of the cooks. This is an unprecedented research.Keywords : Food Processing , Preventive Behavior, Knowledge